An empirical study on the relationship of corporate financial performance and human capital concerning corporate social responsibility: Applying SEM and Bayesian SEM - Hiroki Iwamoto (Taylor & Francis Group, 2019)
The importance of corporate social responsibility (CSR) has increased in corporate strategic management. Thus, this study focuses on three relationships: 1) the relationship between corporate financial performance (CFP) and CSR activities (CSRA), 2) the relationship between CSRA and human capital (HC), and 3) the relationship between HC and CFP. This study uses fact-based data to remove subjective influences as much as possible. Fact-based data include an ordinal scale such as the presence or absence of specific measures. In addition, since it is assumed that the three relationships are mutually affected, this study analyses them simultaneously to consider a mediating effect. In this analysis, structural equation modelling (SEM) and Bayesian SEM (BSEM) are applied to fact-based data collected from 219 listed companies in Japan. The analysis results clarify that CSRA directly impacts CFP and mediates the impact of HC on CFP. In addition, the path value of CSRA to CFP is larger in BSEM than in SEM. Thus, this study shows the merit of using a method that can handle ordinal scale indicators.